Cyberhate the far right in the digital age - Bacigalupo, James, 1987-; Borgeson, Kevin; Valeri, Robin Maria (Lexington Books, 2022)
"Cyberhate: The Far-Right in the Digital Age explores the online world of right-wing political extremism through the propaganda, funding mechanisms, online subcultures, violent movements, and the ideologies that drive it"--